Efektivitas Pendekatan Rational Emotive Therapy dalam Konseling Individual untuk Meningkatkan Kepercayaan Diri Siswa SMK - Ririn Andriani; Hasgimianti Hasgimianti (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2020)
This research was instigated by many of student lack self-confidence. It aimed at knowing  student sel-confidence before and  after giving individual counseling service with Rational Emotive Therapy approach. The approach of this research using quantitative with pre-experimental and the one group pre-test and post-test design. 275 students of  Telecommunication of Vocational High School Pekanbaru was the population in this research. 7 students’s  having low self- confidence were the samples through Purposive Sampling technique. Questionnaire and documentation were the instruments of collecting the data. The data analysis, the researcher uses Wilcoxon’s test. The research findings showed that student self-confidence  before giving individual counseling service with Rational Emotive Therapy approach was on very low category  with the percentage 48.04% and after giving individual counseling service with Rational Emotive Therapy approach, it increase to 73.58%, so, it could be said that there was a difference pre-test and post-test. Based on the data result, it could be concluded that Rational Emotive Therapy approach in Individual Counseling effective to increase student self-confidence that could be seen from the asyimp. Sig (2-tailled) 0.018<0.05 so that H0 was rejected